2010
DOI: 10.1002/cbic.201000237
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Amyloid‐β Peptide(1–42) Oligomerization and Toxicity by Fluorinated Nanoparticles

Abstract: The amyloid-beta peptide (Abeta) is a major fibrillar component of neuritic plaques in Alzheimer's disease brains and is related to the pathogenesis of the disease. Soluble oligomers that precede fibril formation have been proposed as the main neurotoxic species that contributes to neurodegeneration and dementia. We hypothesize that oligomerization and cytotoxicity can be repressed by nanoparticles (NPs) that induce conformational changes in Abeta42. We show here that fluorinated and hydrogenated NPs with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 64 publications
(75 reference statements)
4
65
0
Order By: Relevance
“…This study confirms the fibrillation‐inhibiting effect of charged micelles. Other charged nanoparticles (NPs) were shown to have also a fibrillation‐inhibiting effect . Liao et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirms the fibrillation‐inhibiting effect of charged micelles. Other charged nanoparticles (NPs) were shown to have also a fibrillation‐inhibiting effect . Liao et al .…”
Section: Discussionmentioning
confidence: 99%
“…Saraiva et al . demonstrated that fluorinated NPs promote an increase in the α‐helical content of the Aβ (1‐42) peptide and have an antioligomeric effect . Sulfonated and sulfated polystyrene NPs, which are negatively charged polymeric nanostructures, also affected the conformation of Aβ and induced an unordered state, delaying the peptide oligomerization .…”
Section: Discussionmentioning
confidence: 99%
“…AD is the most common disease in the elderly population. To date, no effective treatment methods to AD have been given [5] . However, three approved treatments for AD should be directed toward decreasing Aβ production, increasing Aβ removal, and preventing Aβ fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…Also they can be able to interact with residues in their vicinity by exploiting the same intermolecular interaction as in Aβ assembly and disrupting the potential for further aggregation [148].…”
Section: Fluorine Incorporation Methodsmentioning
confidence: 99%